The Impact of the United States Withdrawal from the Paris Agreement on the EST Innovation: Evidence from Patent Data - Anuva, Tafsi Islam (2022)
The announcement of the United States withdrawal from the Paris Agreement, also known as the Paris Climate Accords, has influenced the innovation in the United States since 2017. This dissertation paper aims to bring to light the impact of this announcement on the innovation related to environmentally sound technologies (EST) to depict a better understanding of the magnitude of the effect and the plausible reasons behind it. In addition to that, the purpose of this research is to shed light on the insights regarding the drift in the innovation measures and the shift in the R&D investment of the EST innovation. The sample data for this study was collected through the past patent information of firms from the United States for the period of 2011 to 2020. The reason behind conducting a study on the EST innovation in terms of the effect of the withdrawal announcement has briefly been discussed in this paper. The EST innovation aligns with the objectives of the Paris Climate Accords. Thus the withdrawal from this agreement might hinder the EST innovation and its patenting activities in the United States. Therefore, studying the differential effect on the innovation measures- in other words the patent quantity and patent quality, after the announcement, helps to understand the aftershock of this withdrawal. These findings indicate there is a decreasing trend in the patent quantity, patent quality and the R&D investment after the announcement; leading towards the conclusion that this withdrawal announcement has exerted an adverse shock on the EST innovation.